Effect of emulsion temperature on physical properties of palm oil‐based margarine - Miskandar, M. S.; Che Man, Y. B.; Yusoff, M. S. A.; Abdul Rahman, R. (Wiley, 2002)
Margarines made from refined, bleached, and deodorized palm oil at different emulsion temperatures showed no significant difference in their consistency, polymorphic behavior, and solid fat content (SFC) during storage, although differences were observed during processing. The emulsion temperatures studied were 40, 45, and 50°C, with other parameters such as emulsion flow rates, tube cooler temperature, and pin rotor speed kept constant. The SFC developed during processing and storage at 28°C was measured to evaluate the quality of margarine. The emulsion contained no SFC at any emulsion temperature studied. However, the amount of SFC in the perfector or tube cooler unit increased to 15.9, 13.9, and 15.6% in margarine produced at emulsion temperatures of 40, 45, and 50°C, respectively. At 40°C, the lowest SFC was developed during storage even though this margarine had the highest consistency. The softening point of this sample was moderately high and closely related to the type of crystal developed, which was a mixture of β′ and β crystals. Emulsion at 45°C gave the most stable margarine consistency and SFC with crystal in the β′ form even after the fourth week. At 50°C, moderately soft product was produced, which might be undesirable for some applications, although the crystals were in the β′ form.